Elastic scattering measurements of 7Be+natZr at sub- and near – barrier energies - Pakou, Athena (HNPS Advances in Nuclear Physics, 2023)
We will present a recent experiment for elastic scattering of 7Be+natZr at five sub – and near- barrier energies, namely at 21.5, 22.5, 24, 27 and 28 MeV, for determining the optical potential. The experiment was performed at the TriSol radioactive beam facility of Notre Dame University, simultaneously with elastic scattering and breakup measurements of 8B+90Zr , the last performed at 28MeV. This optical potential will be used as one of the coupling potentials in our CDCC calculations for 8B. Further more we will look for the energy dependence of the potential and its resemblance to either the one exhibited by 7Li or the one by 6Li, extracting useful conclusions about their structure. Preliminary data are presented and discussed.